Implementation of Moral Education Values According to Umar bin Ahmad Baradja - Elida Jasman; Rehani Rehani; Sasmi Nelwati; Yunus Rahawarin; Weti Susanti; Yusrial Yusrial (Nida Al-Qur'an: Jurnal Pengkajian Islam, 2023)
This article aims to describe the implementation of moral education values ??according to Umar bin Ahmad Baradja. This research is a qualitative descriptive study. The research results revealed, First, the implementation of the concept of moral education towards Allah SWT according to Umar bin Ahmad Baradja is implemented with activity; i) hum the reading Asma’ul Husna in the field together guided by the class in turns each day, ii) praying during the ceremony led by one of the students, iii) starting class learning by reading prayers and verses from the Quran, iv) praying five times in congregation for the students residing and midday prayers in congregation for all students, v) tahfizh and tadarus of the Quran, vi) implementation of tahtim, vii) gersah (Saturday alms movement). Second, implementation of the concept of moral education for the Prophet according to Umar bin Ahmad was implemented by; i) muhadharah and sermon activities, ii) hadrah activities, iii) activities for the Prophet's birthday and Isra' Mi'raj. Third, the implementation of Islamic morals among students towards their parents is implemented through; i) pray for your parents, ii) be serious about studying, iii) live independently and simply. Fourth, that the implementation of Islamic morals among students towards teachers is implemented by; i) speak politely and answer the teacher's greetings by standing, ii) do not sit in the teacher's place.